Trust and the community of inquiry. Issue 2 (28th January 2018) - Haynes, Felicity
Abstract: This article investigates the place of trust in learning relations in the classroom, not only between teacher and student, but also between student and student. To do this, it will first examine a pedagogy called community of inquiry, espoused by John Dewey and used in most Philosophy for Children courses in Australia. It will then consider what different forms of trust are involved in other power relations in the classroom, particularly the rational structuralism of R.S Peters, or the experiential philosophy of Maria Montessori. It concludes that a community of inquiry shifts the ethical learning relation in significantly different ways because for educational growth, it values ethical trust more highly than a strategic trust in logical principle, duty, Truth, or cost/benefit analysis.